Mapping the Emerging Ecology of Interspecies Coexistence - Tamilroja T,; Dr.Gunanidhi P N, (International Journal of Scientific Research in Science and Technology, 2024)
The world we live in demands more than we are capable of, resulting in technological advancements. From the usage of computers, mobile phones and the internet to genetic modification, downloading of human consciousness, cloning and cryonics, there is an endless list that overflows with novel innovations being added to it every day. When humanoid robots become the “new humans” who will live along with the human species called Homo sapiens, there will exist a “new ecology”. This “new ecology” will become an ecosystem that includes cyborgs, genetically modified children and probably robots with human emotions. With evolving concepts of posthumanism, transhumanism, post-anthropocentrism and post-dualism, literature is shifting from science fiction to something apart from science fiction. This paper will analyse the environment portrayed in Mathieu Bablet’s Carbon & Silicon, a graphic novel, where robots are trying to become humans and humans becoming more like machines.
Keywords: Graphic novel; Ecology; New Ecology; Posthumanism; Transhumanism; Robots; Science Fiction